A Novel Method of Cooperating with Natural Ventilation and Heat Pump to Control the Thermal Noise of Super High-rise Elevator Shaft - Chun Liang; Gong Guangcai; Nie Meiqing; Fang Xi; Li Gaofeng (Zhileng xuebao)
The chimney effect in a super high-rise elevator shaft is significant in winter, which may cause difficulty in opening and closing the elevator doors and can produce obvious aerodynamic noise. In this study, the improvement effect of different cooling methods on the elevator shaft chimney effect is analyzed, including natural ventilation cooling with air volume of 2.12–6.68 m3/s, a radiant cooling panel with height of 10 m and temperature of 10 ℃, and a variable refrigerant volume cooling system (VRV) with cooling capacity of 20–100 kW. A super-high-rise elevator shaft thermal noise control scheme is proposed that combines natural ventilation and heat pump technology, and the feasibility of the proposed scheme is verified through on-site tests. The results show that when both natural ventilation and VRV systems are adopted, the pressure difference between the two sides of the elevator door is 49 Pa less than when only the natural ventilation system is adopted, and is 20.4 Pa less than when only the VRV system is adopted. At the same time, when both natural ventilation and the VRV system are adopted, the noise is 2.1dB less than that when only the natural ventilation scheme is adopted, and it is 1.6 dB higher than the noise when only the VRV system is adopted. Therefore, the simultaneous use of natural ventilation and VRV cooling systems can effectively reduce the chimney effect and simultaneously control the noise in the elevator shaft.